The production of lightweight aggregates using ordinary Portland cement - Hamizi Yahya (School of Environmental Engineering, 2013)
The research study covers the production of lightweight aggregates using Ordinary Portland cement (OPC) without involved any heat treatment. The main aim of this research was to produce lightweight aggregate as artificial aggregate which can be used to replace natural aggregate such as granite in concrete.